Efficacy and safety of the activin signalling inhibitor, sotatercept, in a pooled analysis of PULSAR and STELLAR studies - Höper, Marius; Gomberg-Maitland, Mardi; Badesch, David B.; Gibbs, J. Simon R.; Grünig, Ekkehard; Kopeć, Grzegorz; McLaughlin, Vallerie V.; Meyer, Gisela; Olsson, Karen M.; Preston, Ioana R.; Rosenkranz, Stephan; Souza, Rogerio; et al. (European clinical respiratory journal, 2025)
GRAPHICAL ABSTRACT Overview of the study. # : p<0.001 for comparison of sotatercept with placebo on the basis of aligned-rank stratified Wilcoxon test, stratified according to randomisation factors of background therapy (monotherapy or dual therapy versus triple therapy) and baseline World Health Organization functional class (WHO FC) (II versus III); ¶ : p<0.001 for comparison of sotatercept with placebo on basis of a Cochran–Mantel–Haenszel method, stratified according to randomisation factors. 6MWD: 6-min walk distance; PAH: pulmonary arterial hypertension; PVR: pulmonary vascular resistance.
Gesehen am 04.11.2025